Novel core in cup (In-lay) tablets of lamotrigine for mucoadhesive drug delivery system (International Current Pharmaceutical Journal, 2016)
Lamotrigine a BCS class II drug used in treatment of epilepsy has several disadvantages when taken orally (first pass metabolism and increased Cmax). The aim of the study is to design core in cup (In lay) buccoadhesive tablets which aims for controlled, unidirectional release, increased patient compliance and decreased side effects. The present study involves the preparation of core in cup tablets containing release retarding polymers like sodium alginate, xanthan gum and HPMC E 15LV in core and HPMC K 15M in cup for mucoadhesion. L9 orthogonal array Taguchi design was constructed for the study. The dependent variable studied for L9 orthogonal array Taguchi runs include % drug release from which the formulation with highest S/N ratio was optimized. All the runs were evaluated for physical parameters, drug release, mucoadhesive studies and assay. L1, L2, L4 and L8 formulations showed controlled release for up-to 8 hours with good assay values. The model dependent kinetics showed zero order kinetics with super case II transport and Hixson Crowell mechanism which indicates unidirectional drug release.Srinija and Lakshmi, International Current Pharmaceutical Journal, January 2016, 5(2): 9-13